PsycEXTRA Dataset 2012
DOI: 10.1037/e562352012-001
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look at Driver Education in America

Abstract: The objectives of this study were to: (1) identify and review current driver education and training programs in use nationally and internationally; (2) identify best teaching practices for teenagers; (3) examine the optimal sequencing for the presentation of safe driving skills in the classroom and behind-the-wheel training; and (4) assess whether a new approach to driver education would be beneficial. These objectives were accomplished using a survey of the driver education rules and practices in the 50 State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…[10,12]. Such a conclusion, however, may not be warranted based on these finding because of study limitations.…”
Section: Safety Performance: Survey Participantsmentioning
confidence: 61%
See 2 more Smart Citations
“…[10,12]. Such a conclusion, however, may not be warranted based on these finding because of study limitations.…”
Section: Safety Performance: Survey Participantsmentioning
confidence: 61%
“…Although DE provides an efficient means to learn how to drive, until recently, past evaluations have generally failed to show that such formal programs produce safer drivers [3][4][5][6][7][8][9][10][11][12][13]. This is the case in evaluations of the safety effects of DE that have been conducted internationally, and not just in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that a mandatory driver education requirement had a small but significant association with fewer fatalities in 15-17 year olds. Recent comprehensive reviews of these studies can be found in Lonero and Mayhew (2010), Peck (2011), and Thomas et al (2012).…”
Section: Early Studies Of Driver Educationmentioning
confidence: 99%
“…Driver education programs for teen drivers are designed to prepare beginning drivers for license testing and licensing (Mayhew et al, 2014;Thomas et al, 2012). Driver education courses typically combine both classroom instruction on topics such as vehicle safety, laws and regulations, vehicle operation, and factors affecting driving (alcohol, road conditions, distraction, etc.…”
Section: Introductionmentioning
confidence: 99%